Medieval empires and the culture of competition: Literary duels at Islamic and Christian courts - England, Samuel (Edinburgh, UK: Edinburgh University Press, 2017)
"A probing inquiry into medieval court struggles, this book shows the relationship between intellectual conflict and the geopolitics of empire. It examines the Persian Buyids' takeover of the great Arab caliphate in Iraq, the counter-Crusade under Saladin, and the literature of sovereignty in Spain and Italy at the cusp of the Renaissance. The question of high culture--who best qualified as a poet, the function of race and religion in forming a courtier, what languages to use in which official ceremonies--drove much of medieval writing, and even policy itself. From the last moments of the Abbasid Empire, to the military campaign for Jerusalem, to the rise of Crusades literature in spoken Romance languages, authors and patrons took a competitive stance as a way to assert their place in a shifting imperial landscape."--Back cover.
Introduction: courtly gifts, imperial rewards -- 'Baghdad is to cities what the master is to mankind': the rise of vizier culture -- The sovereign and the foreign: creating Saladin in Arabic literature of the Counter-Crusade -- Alfonso X: poetry of miracles and domination -- Saladino Rinato: Spanish and Italian courtly fictions of Crusade -- Conclusion: the Ministry of Culture.
Includes bibliographical references (pages 188-224) and index.
Keywords: Courts and courtiers -- History -- To 1500.; Authors, Medieval -- Language; Christianity; Muslim; Language and languages -- Political aspects -- History -- To 1500.; Politics and literature -- History -- To 1500.; Literature, Medieval -- History and criticism